Galanin(1-15) and Naltrexone: A novel approach for alcohol use disorder in rats, involving the mesolimbic system. - Flores Gómez, Marta; García-Cantero, Noelia; Pineda-Gomez, Juan Pedro; Moh-Ahmed, Amel; Flores-Burgess, Antonio; Díaz-Cabiale, Zaida; Millón-Peñuela, Carmelo (Elsevier, 2025)
Alcohol Use Disorder (AUD) is a highly prevalent psychiatric and represents a significant public health challenge. Naltrexone (NTX), a mu-opioid receptor antagonist widely used for AUD treatment, has limited efficacy due to side effects and variability in patient response. Interactions between the full-length GAL molecule and the opioid system have been demonstrated. In our recent studies, we showed that the Galanin (1-15) fragment [GAL(1-15)] decreased alcohol seeking along with alcohol consumption. This study aims to examine the effects of GAL(1-15)+NTX on alcohol-seeking behavior and alcohol consumption, as well as the involvement of the mesolimbic system. In rats, we assessed GAL(1-15)+NTX in reward-seeking and the role of GALR2 using the antagonist M871 in the self-administration test. In addition, GAL(1-15)+NTX effects were studied on voluntary alcohol using the two-bottle choice paradigm. Locomotor activity and stereotyped behaviors, along with dopamine release in the dorsal striatum following alcohol injections, were assessed. Moreover, we have analyzed the transcriptional changes of C-Fos, MOR, POMPC, and dopamine receptors in the ventral tegmental area, nucleus accumbens and the hypothalamus. GAL(1-15)+NTX combination reduced alcohol seeking in self-administration and two-bottle choice consumption, with GALR2 involved in the effect. In addition, GAL(1-15)+NTX attenuated alcohol-induced locomotor activity and stereotyped behaviors linked to reduced dopamine release in the dorsal striatum. Notably, these effects were associated with C-Fos, MOR, and dopamine receptor changes, suggesting that the mesolimbic pathway, including the opioid system, is involved in GAL(1-15)+NTX effects. These results open up the possibility of using GAL(1-15) with NTX as a novel strategy in AUD.
Keywords: Alcohol - Consumo; Alcohol - Efectos fisiológicos; Modelos animales en investigación; Neuropéptidos; Naltrexona; Alcohol; Alcohol consumption; Alcohol seeking; Galanin (1−15); Naltrexone